Aplicações das imagens de ressonância magnética no estudo das desordens temporomandibulares - Lopes, Sérgio Lúcio Pereira de Castro [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The temporomandibular joint (TMJ) consist of a diartrodial joint, with remarkable anatomical complexity, and may be influenced by different factors, including anatomical, psychic, and systemic changes. Temporomandibular disorders (TMD) consist of a set of signs and symptoms that characterize the presence of alterations that affect the TMJ, as well as related structures, such as mastigatory muscles. Among the imaging exams that help in the diagnosis of TMD, magnetic resonance imaging (MRI) is the gold standard for this purpose. This imaging modality has, among other advantages being a noninvasive examination, besides the possibility of providing high definition of soft tissues, such as the articular disc and mastigatory muscles, thus being the only imaging technique that enables a high precision study of these structures, besides the anatomical bone components of the TMJ. This thesis compiled 06 studies, published in impact journals, which analyzed the relationship between: anatomical variations of the TMJ structure, the presence of psychological and systemic findings and the use of computational imaging technologies, in order to study the TMJ and possible findings in TMD, using MRI. Two of these studies performed the MRI approach of the TMJ components in individuals with Major Depression (MD) and Migraine (M), in order to investigate the role of psychic and systemic changes in the presence of TMD, observing appears that MD does not appear to be related to factors that would indicate the presence of TMD, but that M would indicate lateral pterygoid muscle hypertrophy and, therefore, could be associated with factors linked to TMD. Regarding the approach of TMD-related anatomical variations, one of the studies reported here investigated the relationship between the articular eminence anatomy of the TMJ and the presence of articular disc displacement, finding a result that reinforced this hypothesis... (Complete abstract click electronic access below)

As articulações temporomandibulares (ATM) consistem numa articulação diartrodial, com notável complexidade anatômica, podendo sofrer a influência de diferentes fatores dentre os quais, os anatômicos, psíquicos, além de alterações sistêmicas. As desordens temporomandibulares (DTM) consistem em um conjunto de sinais e sintomas que caracterizam a presença de alterações que acometem as ATM, bem como estruturas anexas a elas relacionadas, como por exemplo, os músculos da mastigação. Dentre os exames por imagens que auxiliam no diagnóstico das DTM, as imagens por ressonância magnética (RM) constituem no padrão-ouro para esta finalidade. Esta modalidade de imagem apresenta, dentre outras vantagens, a não utilização de energia ionizante, sendo um exame não invasivo, além da possiblidade de fornecer alta definição dos tecidos moles, como o disco articular e músculos da mastigação, sendo assim a única técnica imaginológica que possibilita um estudo de alta precisão destas estruturas, além dos componentes anatômicos ósseos das ATM. Esta tese realizou a compilação de 06 estudos, publicados em periódicos de impacto, que analisaram, a relação entre: variações anatômicas das estrutura das ATM, presença de achados psicológicos e sistêmicos e a utilização de tecnologias computacionais de imagens, com o intuito de estudar as ATM e possíveis achados que suscitassem em DTM, utilizando imagens de RM.Dois desses estudos realizaram a abordagem por RM dos componentes das ATM em indivíduos portadores de Depressão Maior (DM) e de Cefaléia do tipo migrânea (CM), com intuito de se investigar o papel de alterações psíquicas e sistêmicas na presença das DTM, observando-se que a DM parece não estar relacionada com fatores que indicariam a presença de DTM, mas que a CM indicaria uma hipertrofia do músculo pterigóideo lateral e portanto poderia estar associada com ..(Resumo completo, clicar acesso eletrônico abaixo)
Applications of magnetic resonance imaging in the study of temporomandibular disorders
Keywords: Temporomandibular Joint; Magnetic resonance; Radiology; Joint Diseases; Articulação temporomandibular; Ressonância magnética; Radiologia; Artropatias